The Role of Botulinum Toxin for Masseter Muscle Hypertrophy: A Comprehensive Review - Martina Ferrillo; Eleonora Sommadossi; Loredana Raciti; Dario Calafiore; Kamal Mezian; Valeria Tarantino; Michele Vecchio; Umile Giuseppe Longo; Luigi Losco; Alessandro de Sire (Toxins, 2025)
Masticatory muscle hypertrophy (MMH) is a rare clinical phenomenon of uncertain etiology, characterized by a soft swelling near the angle of the jaw. This abnormal enlargement of the masseter muscle can alter the facial profile, leading to aesthetic concerns. Moreover, MMH may also have significant functional repercussions, including pain in the masseter region, often associated with temporomandibular disorders, fatigue, and discomfort during mastication. Non-conservative approaches offer an effective and minimally invasive solution by inducing localized muscle relaxation and reducing hypertrophy. Botulinum neurotoxin type A (BoNT/A) represents a therapeutic option for managing MMH, considering that injections can effectively reduce the masseter muscle volume, improving both facial aesthetics and related symptoms. Currently, the standard non-surgical management of MMH is BoNT/A injections, although consensus on the average dosage has not been definitely reached; on the other hand, there are data available in the literature about the injection technique of BoNT/A for lower face contouring. Therefore, the present comprehensive review aimed at exploring in detail the role of BoNT/A in the treatment of masseter muscle hypertrophy, describing its mechanism of action, the administration protocols, the clinical effects, and any side effects.